Direct Assessment of Graduate Competencies through Collaboration of Classroom Assessment Technique as The Basic Evidences - Herawati, Agnes (Humaniora, 2011)
Graduate competencies are the combination of knowledge, skills or abilities that play important roles in the successful completion of a task at work. However, that does not mean graduate competencies are proven most in the job occupation. The assessment during four years of undergraduate program will be effective ways to assess the achievement of graduate competencies. In the curriculum process, the graduate competencies are broken down into some related learning outcomes. As the main aims, the learning outcomes should pass some assessment to see the achievement of them and get the feedback. The types of the assessment are based on the needs. The decision of this achievement is based on some analysis through various ways, including analytical rubric and checklist. The achievement of learning outcomes will be analyzed more to see how the graduate competencies have been achieved. The result of this analysis will be the basis of direct assessment of the graduate competencies that will result in the collection of evidences as the feedback of the improvement of the whole curriculum.